(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes modern measurement instruments used to identify heat losses in existing residential buildings. It is shown that heat losses in buildings primarily occur through external structures, such as walls, roofs, windows, doors, and balcony slabs. The study compares the technical specifications, advantages, and limitations of three types of infrared thermographic cameras: Bosch GTC400, UNI-T UTi120S, and UNI-T UTi320E. These devices were tested in practical experiments, particularly in a four-story reinforced concrete panel building, and their effectiveness was evaluated. The results indicate that the UTi320E, with its high accuracy, is the most effective for precise detection of heat losses. While the Bosch GTC400 provided sufficient results for medium-sized objects, the UTi120S proved suitable mainly for small objects and rapid inspections. Based on the research findings, criteria for device selection were developed, and practical recommendations for reducing heat losses were provided. This article is of practical significance for construction specialists, energy organizations, and scientific researchers.